2023
DOI: 10.1007/s43440-023-00501-4
|View full text |Cite
|
Sign up to set email alerts
|

Polypharmacology: promises and new drugs in 2022

Piotr Ryszkiewicz,
Barbara Malinowska,
Eberhard Schlicker

Abstract: Polypharmacology is an emerging strategy of design, synthesis, and clinical implementation of pharmaceutical agents that act on multiple targets simultaneously. It should not be mixed up with polytherapy, which is based on the use of multiple selective drugs and is considered a cornerstone of current clinical practice. However, this ‘classic’ approach, when facing urgent medical challenges, such as multifactorial diseases, increasing resistance to pharmacotherapy, and multimorbidity, seems to be insufficient. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…In many cases, diseases with complex physiopathology are very difficult to be treated by monotargeted therapies, and usually requires concomitant therapies (polypharmacy) that have limitations such as therapy adherence and pharmacological interactions. In contrast, multipronged therapies (polypharmacology) may represent potential pharmacological therapies with better clinical benefits after providing a safe profile in humans and an appropriated target engagement as it is the case of reprofiling therapies with small molecules 50 .…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, diseases with complex physiopathology are very difficult to be treated by monotargeted therapies, and usually requires concomitant therapies (polypharmacy) that have limitations such as therapy adherence and pharmacological interactions. In contrast, multipronged therapies (polypharmacology) may represent potential pharmacological therapies with better clinical benefits after providing a safe profile in humans and an appropriated target engagement as it is the case of reprofiling therapies with small molecules 50 .…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established in pharmacology that the therapeutic effects of many drugs are mediated by a multitude of mechanisms (see Supporting Information 3). Moreover, it was recently shown that “off-target toxicity is a common mechanism of action of cancer drugs undergoing clinical trials”. Having put all of these alongside the fact that even in target-based drug discovery, assessments of therapeutic effects play some role as terminal filters, it can be hypothesized that even for the “target-based” drugs, the therapeutic effects might not be entirely attributable to the scheme of target-based drug discovery. Therapeutic “off-target” mechanisms can be unconsciously and fortuitously selected by the phenotypic terminal filters.…”
Section: Evidence On the Efficiency Of Target-based Drug Discoverymentioning
confidence: 99%
“…However, in theory, the number of useful combinations is unlimited if the molecular structure is properly selected and optimized. Also, in practice, it is most feasible to obtain ligands based on two to five pharmacophores [ 45 ]. Moreover, the drugs regimen of a combination therapy can indicate different absorption and distribution profiles which can affect the treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it's generally easier to optimize the dose for a multi-targeted ligand than to do so separately for the components of the combination therapy regimen. Lastly, the clinical trial approval in a combination therapy requires each drug to be investigated separately, and then in combination with each other which is cost- and time-consuming while, MTDLs are time- & cost-efficient for clinical trials since a single compound is involved in the study [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation